(untitled) (Conferencea, 2023)
The expansion of the possibilities of information technologies makes it possible to influence the socio-political environment of a particular country from afar and to derail it. For this purpose, the most complicated situation is the fact that geopolitical goals, which are manifested in various forms in the international arena, are combined with informational and psychological attacks. Information has become a national wealth of the state, and a strategic resource in the international arena. However, modern information technologies create many conveniences and opportunities in the life of society, but also cause some problems. In most cases, these problems arise as a result of malicious use of information communication tools and their capabilities.